2021
DOI: 10.1021/acsami.1c17678
|View full text |Cite
|
Sign up to set email alerts
|

Water-Dispersible Nanocatalysts with Engineered Structures: The New Generation of Nanomaterials for Energy-Efficient CO2 Capture

Abstract: The high energy demand of CO2 absorption–desorption technologies has significantly inhibited their industrial utilization and implementation of the Paris Climate Accord. Catalytic solvent regeneration is of considerable interest due to its low operating temperature and high energy efficiency. Of the catalysts available, heterogeneous catalysts have exhibited relatively poor performances and are hindered by other challenges, which have slowed their large-scale deployment. Herein, we report a facile and eco-frie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Up to now, several techniques have been developed to decrease the energy consumption of the desorption process, such as electrochemically mediated amine regeneration, novel solvent formulas, and catalysts. It is widely acknowledged that the addition of solid acid catalysts can facilitate rapid MEA regeneration at a low temperature without requiring facility modifications, such as zeolites, mental oxides, and solid super acids. In general, metal oxides and solid super acids (SO 4 2– /TiO 2 , SO 4 2– /ZrO 2 , and so on) have stronger acidity, and zeolites possess a comparatively large surface area and centralized pore distribution. A large mesoporous specific surface area and abundant acid sites are both crucial for developing efficient catalysts. , To satisfy these two requirements, supported catalysts have been designed to accelerate MEA regeneration with a lower heat duty.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, several techniques have been developed to decrease the energy consumption of the desorption process, such as electrochemically mediated amine regeneration, novel solvent formulas, and catalysts. It is widely acknowledged that the addition of solid acid catalysts can facilitate rapid MEA regeneration at a low temperature without requiring facility modifications, such as zeolites, mental oxides, and solid super acids. In general, metal oxides and solid super acids (SO 4 2– /TiO 2 , SO 4 2– /ZrO 2 , and so on) have stronger acidity, and zeolites possess a comparatively large surface area and centralized pore distribution. A large mesoporous specific surface area and abundant acid sites are both crucial for developing efficient catalysts. , To satisfy these two requirements, supported catalysts have been designed to accelerate MEA regeneration with a lower heat duty.…”
Section: Introductionmentioning
confidence: 99%
“…Catalyzing is an emerging energy-efficient strategy for amine regeneration at lower temperature (<100 °C). In this regard, solid acid catalysts including zeolites, solid super acids, metal oxides, and their derivatives have been applied to decrease heat duty in the regeneration process. Generally, the acid sites and surface areas are considered to be determining factors for the catalytic performance of the solid acid. ,, Most of the reported solid acid catalysts with abundant acid sites can improve the regeneration rate of monoethanolamine (MEA) by over 30%. , However, a common issue that solid acid catalysts faced is the decreased performance during cyclic tests, making them inapplicable in large-scale industrialization. In view of chemical essence, the basicity of regeneration solution and high regeneration temperature can unavoidably make the degeneration of acid sites to some degree.…”
Section: Introductionmentioning
confidence: 99%
“…Idem et al first reported in 2011 that HZSM-5 and γ-Al 2 O 3 catalysts can be used to optimize the CO 2 desorption from MEA solution and reduce the regeneration energy by 17–24% . Following that, in the past decade, a variety of solid acid materials including metal oxides (ZnO, TiO 2 , Ag 2 O, MoO 3 ), zeolites (H-Y, SAPO-34), sulfated oxides (SO 4 –2 /ZrO 2 /SBA-15), and modified clays (montmorillonite, attapulgite) have been tested to optimize the CO 2 desorption from aqueous monoethanolamine solution at 86–98 °C. Table S1 in the Supporting Information compares the performance of some recent solid acid catalysts for the regeneration of aqueous MEA. Besides the concentration of acid sites, the total surface area and mesoporosity of the used material are also claimed to facilitate the CO 2 desorption reactions . Nonetheless, this is an emerging approach, mainly limited to semiprecious metals and laboriously synthesized solid acidic materials, with reaction mechanisms that are somewhat unclear.…”
Section: Introductionmentioning
confidence: 99%